Monitorization of Acute Brain Dysfunction in Critical Illness - Günseli Orhun; Figen Esen (Galenos Yayinevi, 2016)
Acute brain dysfunction is a clinical condition which is commonly observed in intensive care units and exhibits neurological changes ranging from delirium to coma. Typically observed during sepsis in critical patients, this syndrome is also named as "sepsis-associated encephalopathy" and this situation is of significance since it is related to mortality, increase of morbidity and long-term cognitive impairment. Monitorization of brain functions in critically ill patients should be commenced with detailed neurological examination and effects of sedative drugs, which can alter neurological responses during evaluation, should be taken into consideration. On the other hand, brain imaging methods and electrophysiological examinations are diagnostic procedures which complement neurological examination. While computed tomography enables diagnosis of structural intracerebral lesions, magnetic resonance imaging provides important information on primary pathological mechanisms of sepsis-associated encephalopathy and structural alterations developing in the brain. Evidence of diagnosis and prognosis of acute brain dysfunction can be acquired through use of electroencephalography for. Although it was believed that neurological biomarkers can be useful in determination of diagnosis and prognosis, further studies are needed in this subject.